2022
DOI: 10.1002/jbm.b.35030
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure‐dependent crevice corrosion damage of implant materialsCoCr28Mo6,TiAl6V4andREX734 under severe inflammatory conditions

Abstract: Fretting corrosion is associated with increased risk of premature implant failure. In this complex in vivo corrosion system, the contribution of static crevice corrosion of the joined metal alloys is still unknown. The aim of this study was to develop a methodology for testing crevice corrosion behavior that simulates the physiological conditions of modular taper junctions and to identify critical factors on corrosion susceptibility. Samples of medical grade CoCr28Mo6 cast and wrought alloy, TiAl6V4 wrought al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
(212 reference statements)
0
4
0
Order By: Relevance
“…Finally, it is characterized by a high fatigue strength, mandatory in the cyclic load at which the human body is subjected [3]. However, Herbster et al [26] demonstrated its sensitivity to fretting corrosion, giving an abrasion of the TiO 2 layer that is faster than its repassivation, increasing its susceptibility to fatigue crack initiation. The first group of Ti-6Al-4V specimens employed consisted of those in the supplied state, hereafter named as-received, of bars with a diameter of 20 mm resulting from a hot plastic deformation process.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it is characterized by a high fatigue strength, mandatory in the cyclic load at which the human body is subjected [3]. However, Herbster et al [26] demonstrated its sensitivity to fretting corrosion, giving an abrasion of the TiO 2 layer that is faster than its repassivation, increasing its susceptibility to fatigue crack initiation. The first group of Ti-6Al-4V specimens employed consisted of those in the supplied state, hereafter named as-received, of bars with a diameter of 20 mm resulting from a hot plastic deformation process.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the interplay of degradation products in orthopedic alloys and the body were also a focus. Ongoing concerns related to CoCrMo alloys and the corrosion and wear products were evaluated [87][88][89] including fretting corrosion of modular taper junctions, 90 the effects of chromium degradation products, 90 mixed metal degradation products 89 and crevice corrosion of orthopedic alloys. 87 Three-dimensional printing of soft biomaterials, biomaterial-celldrug combinations and 3D printing of hard biomaterials have all seen increased attention in the past year.…”
Section: Biomaterials Research In Advanced Materials (Ekaterina Peret...mentioning
confidence: 99%
“…Ongoing concerns related to CoCrMo alloys and the corrosion and wear products were evaluated [87][88][89] including fretting corrosion of modular taper junctions, 90 the effects of chromium degradation products, 90 mixed metal degradation products 89 and crevice corrosion of orthopedic alloys. 87 Three-dimensional printing of soft biomaterials, biomaterial-celldrug combinations and 3D printing of hard biomaterials have all seen increased attention in the past year. These works have investigated the range of 3D printing from electron-beam printing of titaniumbased spinal cages 91 to 3D printing of Hydroxyapatite and/or polymeric hydrogel biomaterials.…”
Section: Biomaterials Research In Advanced Materials (Ekaterina Peret...mentioning
confidence: 99%
“…The cell-accelerated corrosion of CoCrMo alloy was also detected under the inflammatory chemical environment generated by particle-stimulated macrophages [ 15 ]. The inflammatory species such as H 2 O 2 , HOCl generated by inflammatory cells can drive the corrosion of implant alloys [ [40] , [41] , [42] ]. The metabolism, adhesion and bioelectricity of inflammatory cells may also regulate the corrosion of metallic implants [ [43] , [44] , [45] ].…”
Section: Introductionmentioning
confidence: 99%